Higher Intake of Dietary Magnesium Is Inversely Associated With COVID-19 Severity and Symptoms in Hospitalized Patients: A Cross-Sectional Study - Nouri-Majd, Saeedeh; Ebrahimzadeh, Armin; Mousavi, Seyed Mohammad; Zargarzadeh, Nikan; Eslami, Mina; Santos, Heitor O.; Taghizadeh, Mohsen; Milajerdi, Alireza (Frontiers in Nutrition, 2022)
Background & Aims: Magnesium is a mineral with anti-inflammatory potential that deserves further attention in COVID-19. We examined the association between dietary magnesium intake and COVID-19 severity and related symptoms in hospitalized patients. Methods: A cross-sectional study was done enrolling 250 COVID-19 patients aged 18 to 65 years. A validated 168-item online food frequency questionnaire was used to assess dietary magnesium intake. COVID-19 Treatment Guidelines were used to determine COVID-19 severity and symptoms were evaluated using a standard questionnaire. Crude and adjusted analyses were performed (Model 1: age, sex, and energy intake; Model 2: Model 1 + physical activity, supplements, corticosteroids, and antiviral drugs; Model 3: Model 2 + body mass index). Results: The mean age of participants was 44.1±12.1 years and 46% of them had severe COVID-19. Patients at the highest tertile of dietary magnesium intake had lower serum levels of inflammatory biomarkers, including CRP (11.8±2.2 vs. 29.5±2.1) and ESR (15.8±2.4 vs. 34.7±2.4) than those at the lowest tertile. After controlling for potential confounders, we observed that a higher intake of dietary magnesium was associated with a lower odds of severe COVID-19 (OR: 0.32; 95% CI: 0.15-0.70). Also, we found a significant inverse association between dietary magnesium intake and odds of COVID-19 symptoms including dyspnea (OR: 0.28; 95% CI: 0.12-0.65), cough (OR: 0.28; 95% CI: 0.12-0.63), fever (OR: 0.35; 95% CI: 0.13-0.93), chilling (OR: 0.34; 95% CI: 0.13-0.92), weakness (OR: 0.14; 95% CI: 0.06-0.34), myalgia (OR: 0.45; 95% CI: 0.21-0.94), nausea and vomiting (OR: 0.03; 95% CI: 0.004-0.24), and sore throat (OR: 0.10; 95% CI: 0.04-0.29). Conclusion: Higher intake of dietary magnesium was inversely associated with COVID-19 severity and symptoms.